Digipreneur Education as the Solution for SMEs Competition in Digital Era - Nugraha, Aryan Eka Prastya (Fakultas Ekonomi, Universitas Negeri Semarang, 2016)
This research aims to create the digipreneur educational model for SMEs and analyze its relationship with developed digital business world.Â The research used the descriptive analysis to explore and clarify a phenomenon. One of the analyses was SWOT analysis method which arrange a plan to achieve both short term goals and long term goals. Based on the constructed model of digipreneur educational model, it is emphasized on business skills aspects where modern financial skill components and all transactions today use e-banking. Digital marketing aspect should be given to SME owners since they need to know that today marketing does not just rely on the physical real world, but also in the fierce competition in digital media as the effective and efficient marketing means. SMEs were resilient business units in anything economic conditions because of their local resources. They had more significant marketing opportunity when their creative products or services were known through the information technology; thus, they need to get the information technology education.